Genetic analysis of agrocin 84 production and immunity in Agrobacterium spp. - Ryder, M H (1987)
Mutations affecting agrocin production on the 48-kilobase (kb) plasmid, pAgK84, can be complemented in trans with cloned portions of the plasmid. Five complementation groups ranging in minimum size from 1.2 to 5.6 kb were identified within a 14-kb segment. Plasmid pAgK84-encoded immunity to agrocin 84 was located to two separate regions of the plasmid. Either region alone was sufficient to protect sensitive strains, and both loci mapped to the agrocin 84 biosynthesis region. One region is located within complementation group I, while the other forms a part of complementation group IV. Production of agrocin 84 was unaffected by nopaline, agrocinopine A, acetosyringone, or low or high levels of ferric iron. Agrocin 84 production was greatly suppressed when the strain also contained a Ti plasmid nutritionally or mutationally derepressed for agrocinopine A catabolism. RNA dot-blot analysis indicated that decreased agrocin 84 production by such strains was not due to transcriptional repression of agrocin 84 biosynthetic loci. In strains also harboring pAtK84b, the opine catabolic plasmid of Agrobacterium radiobacter K84, induction of the agrocinopine A catabolic locus of this plasmid had no such effect on agrocin 84 production.